2007
DOI: 10.1515/cclm.2007.036
|View full text |Cite
|
Sign up to set email alerts
|

Novel molecular defect in the platelet ADP receptor P2Y12 of a patient with haemorrhagic diathesis

Abstract: We conclude that perfusion studies with patient blood are of added value in the diagnostic process, which resulted in identification of a novel molecular defect in the P2Y(12) gene of a patient with haemorrhagic diathesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 9 publications
(8 reference statements)
6
27
0
Order By: Relevance
“…[22][23][24] Our recent study of a novel heterozygous P2Y 12 defect and its association with bleeding in a family with type 1 VWD supports a contribution from other loci to the bleeding tendency in patients with type 1 VWD and provides further evidence for locus heterogeneity in this disorder. 19 In this present study we have identified a patient with type 1 VWD and heterozygous for the P341A mutation.…”
Section: Discussionmentioning
confidence: 67%
“…[22][23][24] Our recent study of a novel heterozygous P2Y 12 defect and its association with bleeding in a family with type 1 VWD supports a contribution from other loci to the bleeding tendency in patients with type 1 VWD and provides further evidence for locus heterogeneity in this disorder. 19 In this present study we have identified a patient with type 1 VWD and heterozygous for the P341A mutation.…”
Section: Discussionmentioning
confidence: 67%
“…Inactivating mutations in P2Y 12 are responsible for bleeding disorders in humans and dogs (Hollopeter et al, 2001;Cattaneo et al, 2003Cattaneo et al, , 2005Shiraga et al, 2005;Remijn et al, 2007;Daly et al, 2009;Fontana et al, 2009;Boudreaux and Martin, 2011). With significant relevance in pathophysiology, P2Y 12 is also the major target of the antithrombotic drugs ticlopidine and clopidogrel.…”
Section: Introductionmentioning
confidence: 99%
“…However, as with the dog in this report, a bleeding tendency has also been documented in people heterozygous for P2Y12 mutations. 9,10 Heterozygosity for a P258T substitution was associated with a lifelong history of severe epistaxis, easy bruising, and excessive posttraumatic hemorrhage in one patient. 10 A bleeding tendency has also been noted in a family that included 3 members heterozygous for a different P2Y12 variant, a K174E mutation, that had been previously diagnosed with type 1 von Willebrand disease (VWD).…”
Section: Discussionmentioning
confidence: 98%
“…9,10 Heterozygosity for a P258T substitution was associated with a lifelong history of severe epistaxis, easy bruising, and excessive posttraumatic hemorrhage in one patient. 10 A bleeding tendency has also been noted in a family that included 3 members heterozygous for a different P2Y12 variant, a K174E mutation, that had been previously diagnosed with type 1 von Willebrand disease (VWD). 9 Therefore, in light of the possibility of VWD occurring with a P2Y12 gene mutation and contributing to the bleeding tendency noted in the dog of this report, plasma VWF:Ag concentration was evaluated 3 times.…”
Section: Discussionmentioning
confidence: 98%